Pelatihan Pengembangan Perangkat Pembelajaran Berbasis Hots Dan Tpack Bagi Guru Sekolah Calon Mahasiswa PPG - Tri Santoso; Ijirana; Sitti Aminah; Magfirah; Sri Mulyani (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Professional teachers must have the ability to develop innovative learning tools that apply the latest learning elements in the 21st century, including TPACK and HOTS. During the program of PPG on the course of developing innovative learning tools, it was found that teachers in elementary, junior high, and high school/vocational, had never gained knowledge regarding the types of innovative learning designs that apply the latest learning elements in the 21st century, especially TPACK and HOTS. Therefore, training on the HOTS and TPACK-based learning tools was carried out. After the training, it was found that the teacher's ability had increased in developing HOTS and TPACK-based learning tools and the participants' responses is good during the training included activeness, participation, motivation, mastery, skills, especially attendance. But questioning skills need to be retrained